(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
The Normalized Difference Moisture Index (NDMI) derived from Sentinel-2A, has been widely used to monitor moisture-related vegetation condition. It was applied to determine the actual impact of Ain Marah wild-fire on the moisture content of the area. Pre and post fire 10 metre Sentinel-2A images, were used to compare water content loss estimation as a result of the fire. NDMI values were tracked for ten months after the fire until 2 months after, in order to determine the moisture variation between the hot and dry seasons. Most recent free cloud Sentinel-2A on the 26th of December 2021, was compared with images taken a day before the fire to examine the moisture recovery over this period. The study results show the vegetation moisture content ranges from low to mid-high water content where vegetation exists, with NDMI values from 0 to 0.3. Whereas 5 months after the fire, the leaves water content represented through NDMI as -0.2 to -0.24 show high water stress over the burnt area. The area moisture content was tracked from August 2020 to August 2021 to examine the dynamics of the vegetation moisture in the burnt area. Although the area is characterized by moderate moisture in the hot season to high moisture in the rainy seasons, the fire caused a significant loss of the vegetation water content until the date of the current study.